2019
DOI: 10.35940/ijeat.a1760.109119
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Fuzzy C-Means Method with Variable FV-TC for Data Sensitivity Calculation in a Cloud Computing Environment

Ashutosh Kumar Dubey

Abstract: In this paper an efficient fuzzy c-means (FCM) method has been used for the data sensitivity estimation. For the saturation point estimation variable fuzziness value (FV)-termination criteria (TC) have been used in the cloud computing environment. Data preprocessing has been performed along with the five attributes. Three attributes are based on the cloud user input parameters and the remaining two are the automated attributes which are calculated automatically. Then FCM has been applied. The total clusters ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…T Multiple Criteria Decision Making (MCDM) models and fuzzy synthesised choices are the foundation of several service choosing methodologies. [21]he findings we have acquired to assess our choice of services offered by the cloud indicated that our model outperforms previous MDMC approaches like TOPSIS, WPM, and the original AHP [17], captures the BDTP extremely well, guarantees Big Data QoS, and scales with the growing number of cloud providers. Through a variety of cloud services from several CSPs, WPM, the SAW, and imposed QoS requirements of Big Data workflows were used [16].…”
Section: International Journal On Recent and Innovation Trends In Com...mentioning
confidence: 92%
“…T Multiple Criteria Decision Making (MCDM) models and fuzzy synthesised choices are the foundation of several service choosing methodologies. [21]he findings we have acquired to assess our choice of services offered by the cloud indicated that our model outperforms previous MDMC approaches like TOPSIS, WPM, and the original AHP [17], captures the BDTP extremely well, guarantees Big Data QoS, and scales with the growing number of cloud providers. Through a variety of cloud services from several CSPs, WPM, the SAW, and imposed QoS requirements of Big Data workflows were used [16].…”
Section: International Journal On Recent and Innovation Trends In Com...mentioning
confidence: 92%